(untitled) (Mediscope, 2021)
Background: Rickettsial diseases are neglected, re-emerging vector borne zoonosis & increasingly considered as one of the most important causes of pyrexia of unknown origin (PUO). They are grossly underdiagnosed due to wide range of non-specific symptoms, low index of clinical suspicion, lack of widely available specific diagnostic tools, leading to significant morbidity & mortality. Appropriate diagnosis in early stages is therefore necessary to prevent fatal complications associated with this disease. Objective: Present study was attempted to assess the burden of rickettsial illness by Weil-Felix agglutination test, among the suspected febrile patients, visiting a tertiary care hospital as well as to analyze the demographic profile & clinical manifestations of the seropositive cases. Methods: This was a cross-sectional study, conducted at department of microbiology, Mymensingh Medical College from March 2018 to February 2019. A total of 453 febrile patients of suspected rickettsial illness, irrespective of age and sex, were enrolled in this study. Serum sample from all the enrolled cases were then analyzed for rickettsial antibodies by Weil-Felix slide agglutination test. Results: Out of 453 cases, a total of 260 (57.39%) showed significant agglutination by Weil-Felix test, of which 101 (38.84%) were reactive to OX2 (spotted fever group rickettsiae), 65 (25%) were reactive to OXK (Scrub typhus) & 13 (5%) showed significant titers to OX19 (typhus fever). Remaining 81 (31.15%) sera were reactive to more than one antigens (mixed reactivity). Seropositivity was higher among female subjects (142; 54.61%) & age group >15-30 accounted for highest number of cases (95; 36.53%). Positive cases showed diverse clinical manifestations like headache (55.76%), myalgia (50.76%), skin rash (10.38%), eschar (9.23%), oliguria (7.3%), jaundice (10.76%), splenomegaly (6.81%), hepatomegaly (7.30%) etc. Conclusion: Rickettsial diseases should be considered as an important etiology of PUO & early diagnosis should be done to initiate proper treatment to prevent fatal complications. Though it lacks sensitivity & specificity, in a resource constraint area like Bangladesh, Weil-Felix test still serves as the cheapest initial diagnostic tool for rickettsial illness to guide the physician for further approaches. Mediscope 2021;8(2): 112-121